1994
DOI: 10.1103/physrevlett.73.3302
|View full text |Cite
|
Sign up to set email alerts
|

Observation of an "Extended" Van Hove Singularity in YBa2Cu4

Abstract: We characterize the nature of the Van Hove singularity near the Fermi energy (E+) in YBa2Cu40& using ultrahigh energy resolution (10 meV) angle-resolved photoemission spectroscopy, together with corresponding first-principles spectra intensity computations.The singularity, related to Cu02 planes, is located about 19 meV below FF at the Y point in the Brillouin zone and arises from a band which is nearly dispersionless along the I to Y direction. Such an "extended" saddle point would render the band structure q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
209
0
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 389 publications
(235 citation statements)
references
References 17 publications
24
209
0
1
Order By: Relevance
“…16 and 15͒ in several copper high-T c oxides which display at least an order of magnitude less dispersion than the first-principles bandstructure methodology can provide. 16 I believe that this flatness is due to the polaron narrowing of the band, Eq. ͑12͒ and the anisotropy is due to the remarkable difference of p x overlaps in x and y direction, respectively.…”
Section: ͑9͒mentioning
confidence: 99%
See 1 more Smart Citation
“…16 and 15͒ in several copper high-T c oxides which display at least an order of magnitude less dispersion than the first-principles bandstructure methodology can provide. 16 I believe that this flatness is due to the polaron narrowing of the band, Eq. ͑12͒ and the anisotropy is due to the remarkable difference of p x overlaps in x and y direction, respectively.…”
Section: ͑9͒mentioning
confidence: 99%
“…A quantitative explanation for a high value of the Hall density in La 2Ϫx Sr x CuO 4 is proposed compatible with the x scaling of dc conductivity. The doping dependence of T c and of H both in underdoped and overdoped samples, the low-temperature dependence of , R H , and H c2 of overdoped Tl 2 Ba 2 CuO 6 and the robust features of ultrahigh energy resolution angle-resolved photoemission spectra 15,16 ͑ARPES͒ are explained with bipolarons.…”
Section: Introductionmentioning
confidence: 99%
“…The inverse mass at the M point is known to be negative and small in the M −Γ direction, and it was suggested that it could be zero, giving rise to an extended van Hove singularity. 59 Here we chose a finite, moderately small value. As we show, the inverse effective mass will decrease when coupling to the spin fluctuation mode is taken into account, and it is this renormalized inverse mass which is experimentally observed.…”
Section: A Theoretical Modelmentioning
confidence: 99%
“…[1][2][3][4] These flat regions in the energy dispersion are directly observed in ARPES experiments on various cuprate compounds. [5][6][7][8][9] Recently, it was also observed in the tunneling spectra of Bi-2201. 10 The presence of saddle points in the energy dispersion is also argued to lead to a superconducting instability in other correlated systems, e.g.…”
mentioning
confidence: 99%